2014
DOI: 10.5430/jha.v3n5p1
|View full text |Cite
|
Sign up to set email alerts
|

Payment method as a predictor of daily distress experienced by physicians

Abstract: Background: Physicians face intrinsic tensions when practicing medicine; therefore, extrinsic factors that could affect distress, such as payment methods, need to be assessed. The study objectives were to: compare levels of distress by payment method, identify factors predicting distress in a two-level regression model, and explore interactions between predictors of distress and payment method. Methods:A cross-sectional study was conducted among physicians in the Saskatoon Health Region, Saskatchewan.Physician… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Implementing effective incentives for physicians to take on administrative duties are challenging since financial payments tend to be viewed as insufficient, respect and prestige conferred by colleagues often being more persuasive. 12 Blended systems have been tried in recent years because no one-payment system can meet all the objectives of complex health systems. 65 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Implementing effective incentives for physicians to take on administrative duties are challenging since financial payments tend to be viewed as insufficient, respect and prestige conferred by colleagues often being more persuasive. 12 Blended systems have been tried in recent years because no one-payment system can meet all the objectives of complex health systems. 65 …”
Section: Discussionmentioning
confidence: 99%
“…9 Physicians who have considerable academic or administrative responsibilities in addition to clinical responsibilities for patients often choose alternative payment plans. 12 The profile of duties for most physicians is about 75% patient care; 15% academic duties, split between teaching and research; and 10% administrative duties, which includes medical practice management duties and serving on professional and health facility committees.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the present study indicate that capitation created assurance in income and reduced physician uncertainty in financial matters, and along with the increased income it created, physicians’ satisfaction was improved. The results obtained by Pena-Sanchez et al also revealed lower levels of distress in physicians who were paid according to the Alternative Payment Plan consisting of both salary and capitation compared to physicians receiving FFC when more than 75% of their patients suffered from complicated conditions ( 29 ).…”
Section: Discussionmentioning
confidence: 98%